KARAKTERISASI pH α-AMILASE Aspergillus versicolor 3a1 YANG DIPRODUKSI PADA MEDIA LIMBAH CAIR TAPIOKA - Aini, Fitratul (Universitas Islam Negeri Raden Fatah, 2012)
The research about pH Chamctarion of Aspergillus versicolor 3a1 a-Amylase Produced on cassava liquid Waste Media was conducted from February 2004-March 2005. The pH thamcteriation of a-amylase Aspergillus versicolor 3a1was done at Labhoratory of Microbiology, Biology Department, Faculty of Maihematic and Natural Science, Bogor Agricultural Univerciy. The aims of this experiments were to produce and to characterize pH of Aspergillus versicolor 3a1a-amilase from cassava liquid waste media. Cassava liquid waste media contains 1 % cassava starcb, 1% yeast extract, 0.13% KH2PO4, and 0.05% MgSO4 diluted in cassava liquid waste. The process pH charactetization of Aspergillus versicolor 3a1 a-amylase was done: isolate regenerition,crude extract production of Aspergillus versicolor 3a1 a-amylase, pH characterization crude extract in ranges 4-9 with optimum temperature and incubation times for 10 minutes. The result proved that a-amylase crude extract from Aspergillus versicolor 3a1 from cassava liquid waste showed its highest specific activity at pH 5; 26.13 U/mg.